2018
DOI: 10.1063/1.5046373
|View full text |Cite
|
Sign up to set email alerts
|

Substantial magnetoelectric coupling in nanocrystalline-Fe2TeO6 at room temperature

Abstract: There is a confocal attention of the multifunctional material science and condensed matter physics research community to the room temperature (RT) magnetoelectric multiferroics through past several decades for its novel physical and chemical properties. Materials with substantial coupling at RT are still an unsaturated problem in the field of condensed matter physics. Apart from searching new magnetoelectrics, enhancement of the coupling as well as physical properties by manipulating the size dependency of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…2(b)-(d)) have clearly indicated the respective charge states. The energy position of the Na 1s (1072.1 eV) clearly reveals the expected 1+ charge state 37 , while the peak positions of Te 3d doublets (576.8 eV, 587.2 eV) along with their energy separation (10.4 eV) suggest 6+ valance state of Te in NCTO 38 . The O 1s spectrum of NCTO has been fitted by considering two singlets (see the green and violet line of Fig.…”
Section: Powdermentioning
confidence: 93%
“…2(b)-(d)) have clearly indicated the respective charge states. The energy position of the Na 1s (1072.1 eV) clearly reveals the expected 1+ charge state 37 , while the peak positions of Te 3d doublets (576.8 eV, 587.2 eV) along with their energy separation (10.4 eV) suggest 6+ valance state of Te in NCTO 38 . The O 1s spectrum of NCTO has been fitted by considering two singlets (see the green and violet line of Fig.…”
Section: Powdermentioning
confidence: 93%
“…Inside each block, spins of magnetic iron ions are collinearly aligned. At the boundary of magnetic blocks, superexchange interactions are responsible for not only setting of the long-range magnetic ordering but also stable helical spin ordering above RT [15][16][17][18][19][20][21][22][23][24][25]63]. From neutron diffraction and magnetization measurement, it is reported that Y-type hexaferrite undergoes ferrimagnetic to conical spin phase accompanied by proper screw phase as an intermediate spin phase manifested in figures 1(c)-(e) [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…ME behavior in all these compounds can be explained by the presence of noncollinear magnetic spins originating due to inverse Dzyaloshinskii-Moriya (DM) interaction [5,13,14].To realize the magnetic control of ferroelectricity in the frustrated magnet systems, alternation or modification in spin state degeneracy is essential [15]. The robust ME coupling at RT is often noticed in antiferromagnets due to presence of strong superexchange interaction in between Fe 3+ ions [16]. Although, the direct quantification of ME coupling (measuring the influence of electrical polarization with magnetic field and vice versa) is not an easy task.…”
Section: Introductionmentioning
confidence: 99%